2008
DOI: 10.1039/b719388b
|View full text |Cite
|
Sign up to set email alerts
|

A new class of functionalized polyoxometalates: synthesis, structure and preliminary antitumor activity studies of three arylimido substituted hexamolybdates bearing a strong electron-withdrawing nitro group, (Bu4N)2[Mo6O18(NAr)] (Ar = 3-NO2-C6H4, 2-CH3-4-NO2-C6H3, 2-CH3-5-NO2-C6H3)

Abstract: Three novel mono-functionalized arylimido derivatives of hexamolybdate bearing the strongest electron-withdrawing nitro group, (Bu(4)N)(2)[Mo(6)O(18)([triple bond]NAr)] (1, 2 and 3), have been synthesized for the first time by an improved reaction of octamolybdate ion and 3-nitroaniline hydrochloride, 2-methyl-4-nitroaniline hydrochloride and 2-methyl-5-nitroaniline hydrochloride respectively with DCC (N,N'-dicyclohexylcarbodiimide) as a dehydrating agent. Complete assignments were achieved for the title compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Preliminary growth inhibition tests also showed that organoimido derivatives of the Lindqvist polyoxomolybdates [Mo 6 O 17 (NAr) 2 ] 2− (Ar = 3-NO 2 -C 6 H 4 , 2-CH 3 -4-NO 2 -C 6 H 3 , 2-CH 3 -5-NO 2 -C 6 H 3 ) have good inhibitory activities against K562 (human leucocythemia) cells, lower than the antitumor drug 5-fluorouracil but better than that of the parent [Mo 6 O 19 ] 2− POM at the same concentration. 11 The anti-cancer activity of polyoxotungstates including organotin 12 and organotitanium 13 substituted heteropolyoxotungstates bearing {Sn(CH 2 ) 2 CN} 3+ or {CH 2 CH(CH 3 )C(O)OCH 3 } 3+ and {CpTi} 3+ groups have also been reported. However, there are very few reports of studies on POMs in which the covalently grafted organic ligand itself possesses a recognized biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary growth inhibition tests also showed that organoimido derivatives of the Lindqvist polyoxomolybdates [Mo 6 O 17 (NAr) 2 ] 2− (Ar = 3-NO 2 -C 6 H 4 , 2-CH 3 -4-NO 2 -C 6 H 3 , 2-CH 3 -5-NO 2 -C 6 H 3 ) have good inhibitory activities against K562 (human leucocythemia) cells, lower than the antitumor drug 5-fluorouracil but better than that of the parent [Mo 6 O 19 ] 2− POM at the same concentration. 11 The anti-cancer activity of polyoxotungstates including organotin 12 and organotitanium 13 substituted heteropolyoxotungstates bearing {Sn(CH 2 ) 2 CN} 3+ or {CH 2 CH(CH 3 )C(O)OCH 3 } 3+ and {CpTi} 3+ groups have also been reported. However, there are very few reports of studies on POMs in which the covalently grafted organic ligand itself possesses a recognized biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…A series of mono‐,, bi‐, and multifunctionalized derivatives of hexamolybdates were successfully obtained by the DCC protocol . It is notable that some arylimido derivatives of hexamolybdates containing strongly electron‐withdrawing functional groups (i.e., –NO 2 and –CF 3 ) were also obtained by this protocol , . Therefore, we utilized DCC as the dehydrating regent in the reactions of arylhydrazides and octamolybdate.…”
Section: Resultsmentioning
confidence: 99%
“…The terminal oxo or bridging oxo atoms (O t ) of POMs can be replaced by alkoxy or organic amine ligand to form corresponding organically derivatized POMs ( Proust et al, 2012 ; Zhang et al, 2019 ). Especially for these derivatives of terminal O t of POMs replaced by organic amine via multiple covalent bond, organoimido derivatives of POMs ( Clegg et al, 1995 ; Strong et al, 2000 ; Wei et al, 2001 ) had received increasing research attention owing to the advantage of bond adding value ( Xue et al, 2008 ). It can not only combine the properties of organic ligands and POMs but also possibly result in new properties due to the conjugation between organic ligands and POMs ( Peng et al, 2004 ; Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%